Superior sagittal sinus thrombosis in the course of mixed phenotype acute leukaemia treated with acute lymphoblastic leukaemia-like therapy—a case report - Wojciech Lizurej; Łukasz Mazurkiewicz; Michał Kowalski; Sylwia Szydłowska; Michał Wyrzykowski; Krzysztof Lewandowski (Thrombosis Journal, 2023)
Abstract Mixed phenotype acute leukaemia (MPAL) is associated with worse overall survival, compared with other acute leukaemias in adults. Lack of clear treatment guidelines makes the therapy challenging. ALL-like induction and consolidation treatment followed by allo-HSCT is the preferred first-line treatment. We present a case of a 36-year-old woman diagnosed with MPAL (EGIL Myelo/B) with KMT2A rearrangement, treated with the PALG-ALL-7 (including PEG-asparaginase) protocol. On day 25 after the induction therapy initiation, numbness of limbs and dizziness were observed. Therefore, the imaging studies (CT and MRI) were performed and a diagnosis of thrombosis of superior sagittal sinus of the brain was established. Routinely performed blood coagulation tests showed prolonged APTT and PT, decreased antithrombin III activity and decreased free protein S concentration. LMWH treatment and substitutional therapy with antithrombin III were started, which resulted in a significant reduction in the thrombosis associated symptoms and improvement of the neurological status after 3 days. After induction and consolidation therapy, the patient obtained complete haematological remission and negative measurable residual disease. Six months after the diagnosis, allo-HSCT was successfully performed. During the 4 months follow-up, the patient remained MRD negative and thrombotic symptoms free. To the best of our knowledge, our communication has been the first report of such complication in an MPAL patient treated with PEG-asparaginase containing protocol in adults. We recommend increased vigilance in patients manifesting any mild neurological symptoms and early decision about the MRI study performance.